Analisis Besaran Insentif Guna Meningkatkan Kinerja Karyawan Pada PT Sumber Alfaria Trijaya Tbk - Aryanti Hopah Nurpadilah; Syifa, Syifa Pramudita Fadila (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Salary is still the most important thing in the life of workers or workers. The amount of salary received can determine the performance provided, sometimes the wages received are not in accordance with the performance provided, therefore the provision of incentive money as additional wages is very important, so that the daily needs of employees are met, and not to impact on their work. The purpose of this study is to analyze how the calculation of the amount of incentives carried out by Alfamart in order to improve employee performance at PT Sumber Alfaria Trijaya Tbk. This research method uses a qualitative descriptive analysis method by using interview data collection techniques, observation and documentation. From the results of the study it was found that there was an increase in performance for employees who received incentives at a predetermined amount, and this amount was quite tempting as evidenced by the presence of personnel who always received PSM.